Influences on the supply of accounting graduates in Australia: A focus on international students - Jackling, Beverley; Keneley, Monica (Accounting and finance (Parkville), 2009)
This paper examines the influences on the potential supply of accounting graduates in Australia with reference to the personal and social influences on the decision to major in accounting using the Theory of Reasoned Action and focusing on differences between local and international students. Responses from 437 accounting majors' found that personal attitudes linked to 'intrinsic interest' and 'extrinsic interest' was influential in choice of major. 'Reference groups' were an important social influence for international students. The findings have implications for government policy and the accounting profession in terms of attracting students and particularly international students, who are sufficiently interested in accounting as a career choice to address the skill shortage in Australia. [Author abstract]